The Financing Structure of Islamic Banks: A Comparative Study - Mardhiyaturrositaningsih Mardhiyaturrositaningsih (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - This study aims to analyse the financing structure of Islamic Commercial Bank and Islamic Business Unit. This Study Compare the financing structure before and during the Covid-19 pandemic.Method - This research is using The comparative research method to determine differences in the financing structure of Islamic Banks before and during the Covid-19 period.Result - The result of this research indicates that the financing structure of Islamic Commercial Banks and Islamic Business Units based on the type of shari’ah compliant contract and the type of usage shows differences before and during the covid-19 pandemic. The decrease is shown in financing with mudharabah and ijarah contracts.Implication - The research indicates that the Bank has been impacted by the Covid-19 pandemic as indicated by changes in the financing structure of the banking system. Banks need to determine the right strategy in this situation.Originality- This study conducted a financing test based on the type of contract and the type of usage. This study identified two conditions in the period before and during the pandemic.